Hydrogen peroxide attenuates rhinovirus-induced anti-viral interferon secretion in sinonasal epithelial cells - Lee, Sang Hag; Han, Mun Soo; Lee, Tae Hoon; Lee, Da Bin; Park, Jae Hyung; Lee, Seung Hyeok; Kim, Tae Hoon (Frontiers in Immunology, 2023)
Altered innate defense mechanisms, including an imbalance between oxidants and antioxidants release, have been implicated in the pathogenesis of chronic rhinosinusitis (CRS). The aim of this study is to investigate whether oxidative stress may attenuate the secretion of anti-viral interferons in human sinonasal mucosa. The levels of H2O2 in nasal secretion were increased in patients with CRS with nasal polyps, compared with that of CRS patients without nasal polyps and control subjects. Normal sinonasal epithelial cells derived from healthy subjects were cultured under an air-liquid interface. The cultured cells were infected with rhinovirus 16 (RV 16) or treated with poly (I: C), TLR3 agonist, after being pretreated with an oxidative stressor, H2O2 or antioxidant, N-acetylcysteine (NAC). Thereafter, the expression levels of type I (IFN-) and type III (IFN-1 and 2) interferons and interferon-stimulated genes (ISGs) were evaluated with RT-qPCR, ELISA, and western blot. The data showed that the production of type I (IFN-) and type III (IFN-1 and 2) interferons and ISGs was upregulated in cells infected with RV 16 or treated with poly (I: C). However, their up-regulated expression was attenuated in cells pretreated with H2O2, but not inhibited in cells pretreated with NAC. In line with these data, the up-regulated expression of TLR3, RIG-1, MDA5, and IRF3 was reduced in cells pretreated with H2O2, but not attenuated in cells treated with NAC. Furthermore, cells transfected with Nrf2 siRNA showed decreased secretion of anti-viral interferons whereas sulforaphane treatment enhanced the secretory capacity of antiviral interferons. These results suggest that the production of RV16-induced antiviral interferons may be attenuated by oxidative stress.